Penggunaan Bahasa Daerah pada Buku Bacaan Siswa Terbitan Kemdikbud - Aisyah Nur Fadhilah; Laili Etika Rahmawati (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2020)
This study aims to identify the use of regional languages in student reading books published by the Ministry of Education and Culture. This type of research is a qualitative descriptive study. The object of research is the local language in the student reading book published by the Ministry of Education and Culture entitled "Kenara Anak Suku Gayo" and "Kain Kulit Kayu Dei". The data from this study are student reading books published by the Ministry of Education and Culture which contain local languages. The data source in this research is an archive or document in the form of a student reading book published by the Ministry of Education and Culture which contains local languages. Data collection techniques use the technique of listening and note taking, the researcher first reads the reading book "Kenara Anak Suku Gayo" and "Kain Kulit Kayu Dei" published by the Ministry of Education and Culture to carefully determine the use of local languages, then record in full and then identify the use of local languages in the book reading. Data analysis techniques using flow analysis. The results showed that the Ministry of Education and Culture has efforts to preserve local languages, use Indonesian, and master foreign languages. The language used in the students' reading book "Kenara Anak Suku Gayo" and "Kain Kulit Kayu Dei" is not purely using Indonesian, but there is interference with local languages. The percentage of the use of local languages in the reading books of "Kenara Anak Suku Gayo" is 40%, while in the reading books of students "Kain Kulit Kayu Dei" 20%.